TRANSFORMATIONAL LEADERSHIP DALAM MENINGKATKAN BREASTFEEDING FATHER TERHADAP IBU MENYUSUI - Khoiriyah, Siti; Setyawati, Ari (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Introduction: Husband's support is also influenced by support from health workers, especially nurses in providing education about the importance of exclusive breastfeeding. For this reason, nurses as educators need a transformational leadership style that is able to provide information to husbands about knowledge of exclusive breastfeeding. Method: The method used in this paper is a literature review study. This literature study analyzes the breastfeeding father and analyzes the transformation leadership and then a synthesis is carried out to describe the effect of transformation leadership on the breastfeeding father on breastfeeding mothers. Results: Leadership transformation can increase breastfeeding fathers for breastfeeding mothers. Conclusion: Transformational leadership can be applied by all nurses in increasing breastfeeding fathers for breastfeeding mothers.